2012
DOI: 10.5604/15093492.992293
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Aspects of Conservative Treatment of Scoliosis – A Theoretical View Point

Abstract: An upright body posture cannot be maintained passively for reasons including a high location of the centre of gravity (COG) and a small support area. Proper alignment of body parts is maintained automatically, tending towards a pattern encoded in the CNS. A particularly important role in posture regulation is played by the short muscles of the back, which respond to being stretched with a contraction. During the early phase of scoliosis, the CNS automatically corrects abnormalities, but over time habituation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…14 The studies evaluating the efficacy of bracing and other conservative therapies are inconsistent, and thus their findings must be regarded as inconclusive. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Several small studies are optimistic about yoga-like media alcanzó un 40,9 %. No hubo diferencias significativas de las mejorías entre los subtipos adolescentes idiopáticos y degenerativos (un 49,6 % y un 38,4 %, respectivamente).…”
Section: Treatment Of Scoliosisunclassified
“…14 The studies evaluating the efficacy of bracing and other conservative therapies are inconsistent, and thus their findings must be regarded as inconclusive. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Several small studies are optimistic about yoga-like media alcanzó un 40,9 %. No hubo diferencias significativas de las mejorías entre los subtipos adolescentes idiopáticos y degenerativos (un 49,6 % y un 38,4 %, respectivamente).…”
Section: Treatment Of Scoliosisunclassified
“…School children spend many hours writing, reading, watching TV and doing homework on a daily basis. Their sitting postures are important, because improper sitting postures may result in progression of spinal curvatures [ 23 ]. Studies have shown that children habitually slumped or when were asked to relax.…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies [2,5,[21][22][23][24][25] discuss its biomechanics, pathogenesis and kinematics. For treatment of scoliosis, two studies [3,8] talk about surgery and fifteen studies [4,[9][10][11][12][26][27][28][29][30][31][32][33][34][35] about different forms of conservative treatment.…”
Section: Resultsmentioning
confidence: 99%
“…One being Postural scoliosis (Grade I), which is without any bony changes or muscular weakness [26]. The causative factor may be the impairment of the postural reflex mechanism or wrong postural habits.…”
Section: Types Of Scoliosis and Its Curvesmentioning
confidence: 99%
See 1 more Smart Citation